Effects of a Multicomponent Herbal Extract on the Course of Subclinical Ketosis in Dairy Cows – a Blinded Placebo-controlled Field-study - Durrer, Manuela; Mevissen, Meike; Holinger, Mirjam; Hamburger, Matthias; Graf-Schiller, Sandra; Mayer, Philipp; Potterat, Olivier; Bruckmaier, Rupert; Walkenhorst, Michael (Planta Medica, 2020)
A blinded placebo-controlled multi-center on-farm trial was conducted in dairy cows with subclinical ketosis to investigate effects of a multicomponent herbal extract. Blood ketone levels were measured weekly in early lactating cows from 16 Swiss herds. Cows were subclassified based on their initial blood-β-hydroxybutyrate levels (≥ 1.0 [KET-low, 84 cows] and > 1.2 mmol/L [KET-high, 39 cows]) and randomly distributed to 3 groups treated orally with herbal extract containing Camellia sinensis, Cichcorium intybus, Gentiana lutea, Glycyrrhiza glabra, Taraxacum officinale, Trigonella foenum-graecum, and Zingiber officinale, sodium propionate, or placebo twice a day for 5 days. Milk yield, milk acetone, blood-β-hydroxybutyrate, glucose, nonesterified fatty acids, gamma-glutamyl transferase, and glutamate dehydrogenase were analyzed over 2 wk. Linear mixed effect models were used for data analysis. No effects were found for nonesterifed fatty acids, gamma-glutamyl transferase, and glucose. Significantly higher glutamate dehydrogenase (29.71 U/L) values were found in herbal extract-treated animals compared to sodium propionate on day 7 (22.33 U/L). By trend, higher blood-β-hydroxybutyrate levels (1.36 mmol/L) were found in the placebo group of KET-high-cows on day 14 compared to the sodium propionate group (0.91 mmol/L). Milk yields of all treatment groups increased. Milking time and treatment showed a significant interaction for milk acetone: sodium propionate led to an immediate decrease, whereas herbal extracts resulted in a milk acetone decrease from day 7 on, reaching significantly lower milk acetone on day 14 (3.17 mg/L) when compared to placebo (4.89 mg/L). In conclusion, herbal extracts and sodium propionate are both likely to improve subclinical ketosis in dairy cows, however, by different modes of action.
Keywords: subclinical ketosis; herbal extract; sodium propionate; dairy cow